Hispanic Caribbean Theatre on the Move: Crossing Borders, Redefining Boundaries - Stevens, Camilla (Latin American Theatre Review, 2017)
This essay reflects on the disciplinary trajectory of a course that I have taught both in foreign languages and literatures and in ethnic studies on the theme of migration in Hispanic Caribbean theatre. Crossing disciplinary borders sharpens our understanding of how theatrical performance has registered the complex social, economic, and political networks that connect the Hispanic Caribbean to the United States. Moreover, I argue that the viewing of Cuban, Dominican, and Puerto Rican theatre through a diasporic and transnational lens helps explain in part its marginalization in Latin American theatre studies, a field still dominated by national frames of reference. Exploring interdisciplinary approaches to teaching Latin American theatre not only resists the “border control” exerted by institutional units and academic disciplines but also helps redefine the field and spotlight its unique contributions to social scientific and humanistic inquiry.